Reproductive Performance of Jabres Cow at Brebes, Central Java Province, Indonesia - Panjono, Panjono; Haq, Miftahush Shirothul; Hanim, Chusnul; Andarwati, Siti; Maharani, Dyah; Widayati, Diah Tri; Budisatria, I Gede Suparta (Springer International Publishing, 2016)
This study was conducted to observe the reproductive performance of Jabres cow at Brebes Regency, Central Java Province. One hundred and seventy four heads of cows were used in this study. Animals were raised by farmers as usual. Feed consumption was observed for 6 days. Birth weight was weighed soon after calves were born. Weaning age, postpartum estrus, postpartum mating, service per conception, gestation period, and calving interval were investigated based on the farmers’ recording. The data collected was analyzed quantitative description. Dry matter (DM), crude protein, and total digestible nutrient intake of cow were 2.32% BW, 11.41% DM, and 60% DM, respectively. Birth weight of Jabres calf was 18.14 kg ± 1.48 kg. Weaning age, postpartum estrus, postpartum mating, service per conception, gestation period, and calving interval of Jabres cow were 191.72 ± 35.30 days, 83.21 ± 19.05 days, 100.22 ± 22.99 days, 1.71 ± 0.80 days, 280.35 ± 17.52 days, and 383.96 ± 21.11 days, respectively. It is concluded that reproductive performance of Jabres cow is quite good. The calving interval can be improved by shortening PPM and decreasing S/C values.